Budget deficit and inflation nexus in Uganda 1980-2016: A cointegration and error correction modeling approach - Kurayish Ssebulime; Bbaale Edward (Journal of Economic Structures, 2019)
Background: One of the principal goals of monetary policy pursued by Central Banks worldwide is virtually price stability. Understanding inflationary dispositions and its determinants is therefore a critical issue from the monetary authorities, scholars and the policy makers viewpoint. The purpose of this paper is to investigate the budget deficit and inflation nexus for Uganda for the period 1980-2016. This is because budget deficit in Uganda has been one of the top topical issues of concern in the country's historical economic problems. The study employs the cointegration and error correction model (ECM) as well as the pairwise Granger causality. This is because the ECM technique has become a tool of choice for estimation and testing the multivariate relationships among the non-stationary data in much of the time series macro-econometrics. Results: Results of the Granger causality test show that budget deficit Granger causes inflation in Uganda at a conventional level of significance. However, no feedback effect is observed. The cointegration results reveal a positive and statistically significant long-run relationship between the series, and the results of the ECM reveal that budget deficit causes inflation in Uganda only in the short run. Further, in Uganda, budget deficit affects inflation directly and indirectly through fluctuations in the nominal exchange rate and money supply. Conclusions: The main conclusion from this analysis is the existence of the long-run relationship among inflation, budget deficit and money supply. This was thus an indication of Granger causality in at least one direction among the variables. However, the impact of trade balance and exchange rate were taken as exogenous. A long-run stationary relationship between the budget deficit, money supply, inflation, trade balance and the exchange rate has been found to hold for Uganda. The major implications for this study are that inflation in Uganda is caused by both monetary as well as fiscal factors. A comprehensive policy package involving budgetary, monetary as well as exchange rate policies is required to deal with inflation.
Keywords: 330; Budget deficit; Inflation; Granger causality; Error correction model; Uganda